THE ROLE OF ISLAMIC EDUCATION IN ADVANCING SOCIAL TRANSFORMATION THROUGH CHARACTER STRENGTHENING AND COMMUNITY EMPOWERMENT - Icang Tatan Tiana; Fida Fadilatul Romdoniyah; Muhammad Hilmy Ibnu Muqti; Ade Nurmaliyani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
In the era of globalization and digitalization, society faces serious challenges in the form of moral degradation, identity crises, and weak social solidarity due to the dominance of materialistic values. In addition, many Islamic educational institutions, especially Islamic boarding schools, still lack development in the areas of economics and life skills for students, so they have not been able to play an optimal role in promoting community independence and social transformation. In fact, Islamic education should ideally function not only as a moral fortress, but also as a means of empowering the community based on spiritual and social values. This study aims to analyze the role of Islamic education in promoting social transformation through character building and community empowerment. The research was conducted at the An-Nur Malangbong Garut Foundation, an Islamic educational institution that integrates formal education, Islamic boarding school curriculum, and productive economic activities based on Islamic values. A qualitative approach was used with a case study method, through interviews, observation, and documentation. The results show that Islamic education at the An-Nur Foundation plays a strategic role in shaping the character of a transformative generation through the internalization of Islamic values, the integration of the national and pesantren curricula, and the implementation of life skills and entrepreneurship programs. Managerially, the institution applies a participatory management pattern that involves teachers, students, and the community in every stage of program planning and evaluation. This strategy not only strengthens the religious and social character of students, but also increases economic independence and community participation in religious and social activities. This study confirms that Islamic education that is managed in a participatory manner and based on community empowerment can be a driving force for sustainable social transformation in the modern era.